Total neoadjuvant therapy based on short-course radiotherapy versus standard long-course chemoradiotherapy for locally advanced rectal cancer: a systematic review and meta-analysis of randomized controlled trials - Pu, Wenji; Chen, Wenqi; Jing, Haiman; Li, Jishi; Jiang, Yong; Li, Shasha; Wen, Weijie; Xu, Zhiyuan; Jin, Jing (Frontiers in Oncology, 2024)
BackgroundWe conducted the meta-analysis to compare the therapeutic effects of total neoadjuvant therapy (TNT) based on short-course radiotherapy followed by consolidation chemotherapy (SCRT/CCT) and long-course chemoradiotherapy (LCCRT) for locally advanced rectal cancer (LARC) according to certain significant randomized controlled trials (RCTs).MethodsThe researchers retrieved several databases, including PubMed, Embase, Web of Science, and the Cochrane Library, to collect all the relevant literature published since the establishment of the databases until July 30, 2024, and then screened to determine the qualified literature and extracted the relevant information. Finally, RevMan 5.4 software was utilized to conduct the meta-analysis for determining the 95% confidence interval (CI) and pooled risk ratio (RR). There were 9 study indicators, including the pathologic complete remission (pCR) rate, tumor downstaging rate, R0 resection rate, sphincter preservation rate, disease-free survival (DFS), overall survival (OS), acute ≥3 grade toxicity rate, surgery complication rate, and distant recurrence rate. When moderate, even severe, heterogeneity was found, a random-effect model was applied; otherwise, a fixed-effect model was used for the analysis.ResultsA total of 6 eligible RCTs and 2259 participants were included in this meta-analysis. Compared with the standard LCCRT, TNT treatment on the basis of SCRT/CCT increased the pCR rate significantly [RR = 1.67, 95% CI (1.36, 2.04), P < 0.00001], especially in ≥ 4 cycles of the CCT arm [RR = 1.77, 95% CI: (1.41–2.23), p < 0.00001], and led to a similar tumor downstaging rate [RR = 0.99, 95% CI (0.85, 1.15), P = 0.92]. Moreover, survival outcomes, distant recurrence rate, and surgical indicators were comparable between the two groups.ConclusionFor LARC patients, the SCRT/CCT regimen not only has a higher pCR rate, equivalent OS, and comparable additional indicators versus standard LCCRT but also shortens the treatment time, costs less, and improves patients’ adherence to the innovative anti-tumor therapy; hence, with the concept of acute toxicity control, it could be further widely and safely utilized, especially in resource-limited settings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024600180.